2023
DOI: 10.26434/chemrxiv-2023-wrq5d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Access to Free Phenols by Photocatalytic Acceptorless Dehydrogenation of Cyclohexanones at Room Temperature

Abstract: Phenols are ubiquitous substructures in natural products and bioactive compounds. However, practical methods for the direct construction of phenols under mild conditions remains challenging. Herein, a photocatalytic acceptorless dehydrogenative aromatization of cyclohexanones or cyclohexenones at room temperature has been developed. The reaction features the visible-light and cobalt co-catalyzed sequential dehydrogenation of in-situ formed enol silyl ethers, which are regarded as a challenging process. This op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Using 2,6-lutidine as base delivered 2 in 81% yield, yet the uses of other organic or inorganic bases, such as DABCO, DIPEA and KOAc were totally ineffective (Table 1, entries [11][12][13][14]. Solvent effect evaluation revealed that both 1,2-dichloroethane (DCE) and dichloromethane (DCM) are good solvents for this reaction, allowing the formation of 2 in 77% and 61% yields (Table 1, entries [15][16][17]. Control experiments showed that light, photocatalyst and Co-catalyst are essential to this phenol synthesis (Table 1, entries 18 and 19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using 2,6-lutidine as base delivered 2 in 81% yield, yet the uses of other organic or inorganic bases, such as DABCO, DIPEA and KOAc were totally ineffective (Table 1, entries [11][12][13][14]. Solvent effect evaluation revealed that both 1,2-dichloroethane (DCE) and dichloromethane (DCM) are good solvents for this reaction, allowing the formation of 2 in 77% and 61% yields (Table 1, entries [15][16][17]. Control experiments showed that light, photocatalyst and Co-catalyst are essential to this phenol synthesis (Table 1, entries 18 and 19).…”
Section: Resultsmentioning
confidence: 99%
“…Next, aryl fused cyclohexanones were tested. Electron-withdrawing and electron-donating groups on aromatic rings can be tolerated, affording corresponding 1-and 2-naphthol products (17)(18)(19)(20)(21)(22)(23)(24)(25) in 50%-92% yields. Moreover, heterocycles including thiophenes (12 and 26), furans (13) and pyrroles ( 27), were also compatible in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation